PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP SUSTAINABILITY DISCLOSURE - Rr. Naidia Astrinita Wulandari; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
This study aims to analyze the effect firm size, profitability and leverage to sustainability disclosure. Firm size, profitability, and leverage as independent variables is measured using a log from total aset, ROA, and book value of financial debt to total assets ratio. Sustainability disclosure acts as a dependent variable measured using GRI values. The sample in this study is based on companies listed on the Indonesia Stock Exchange which issued sustainability disclosure in 2013-2015. Sample selection method used is purposive sampling method. This research uses analytical technique that is ordinary least square. The results revealed that the firm size positively affect sustainability disclosure. However, profitability and leverage has no effect on sustainability disclosure.